Answer:
f(x) has moved:
4 units in the positive y direction i.e upwards
3 units in the positive x direction
Step-by-step explanation:
to get g(x), f(x) has undergone the following transformations
f(x) = x³
f1(x) = x³ + 4 (translation of 4 units in the positive y direction i.e upwards)
f2(x) = g(x) = (x-3)³ + 4 (translation of 3 units in the positive x direction i.e towards the right)
Answer:
Step-by-step explanation:
1 yes 2 no 3 no 4 yes 5 no
2. f(x) = x - 2x² - 5 + 10x
=-2x² + 8x - 5
f'(x)= -4x + 8
4. y = 100(45x - 30 - 3x³ + 2x²)
= 100(-3x³ + 2x² + 45x -30)
= -300x³ + 200x² + 4500x - 3000
y' = -900x² + 400x + 4500
Answer: B- 1 1/9
Work:
5 2/3 - 4 5/9
1 2/3 - 5/9
1 6/9 - 5/9
= 1 1/9
Answer:
Step-by-step explanation: